2012
DOI: 10.4314/wsa.v38i4.15
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen, phosphorus and silicon in riparian ecosystems along the Berg River (South Africa): The effect of increasing human land use

Abstract: The Berg River is one of the main rivers in the Cape Region; it is essential for the local economy and ecology, as it supplies water to agriculture and industries, provides drinking water for the greater Cape Town region, and supports rich aquatic ecosystems. The Berg River is impacted by both diffuse pollution from agricultural run-off and point-source pollution from urban and industrial wastewater. Construction of a dam on the headwaters of the Berg River in 2007 has changed the hydrology of the upper catchm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Sharpley et al 2000 ; Cordell et al 2009 ). Struyf et al ( 2012 ) found a twofold increase in P concentration in the sediment of the Berg River, South Africa, under increasing human influence. Phosphorus is a non-renewable resource and therefore P losses are detrimental to the long-term sustainability of agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Sharpley et al 2000 ; Cordell et al 2009 ). Struyf et al ( 2012 ) found a twofold increase in P concentration in the sediment of the Berg River, South Africa, under increasing human influence. Phosphorus is a non-renewable resource and therefore P losses are detrimental to the long-term sustainability of agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…In light of De Villiers 2007, it is of concern to note the findings of Struyf et al (2012), who investigated the changes in riparian nutrient dynamics along the Berg River. They found that nutrient concentrations in the sediments within the riparian zone reflect the concentrations of nutrient in the Berg River.…”
Section: Resultsmentioning
confidence: 99%
“…Struyf et al (2012) highlighted that their study indicated that if the changes in the hydrological cycle, in particular reduced flow, and water quality levels suggested in De Villiers (2007) were to come to fruition, it would be highly likely that a number of ecosystem goods and services would be impactedincluding the natural filter function of the river system. Furthermore, Struyf et al (2012) suggest that due to the impact of the high nutrient levels on the riparian zone, it may in future become a source of nutrients for the river, further compounding the challenges in managing the river. Paulse et al (2007) utilised a section of the Berg River to compare different enumeration techniques for the investigation of bacterial pollution.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such gaps in knowledge lead to our inability to model silica dynamics on regional or continental scales, as demonstrated by Lauerwald et al (2013). One reason that floodplain and riparian processes are poorly understood is that, although we know many plants create siliceous phytoliths in their biomass (e.g., Conley 2003; Cary et al 2005; Struyf et al 2012), we know little about how and whether those phytoliths accumulate in the oft‐saturated soils of riparian zones. Another challenge in quantifying riverine silica sequestration is that riverine sediments are notoriously difficult to date because riverine sedimentation is spatially and temporally discontinuous.…”
Section: Introductionmentioning
confidence: 99%